2004
DOI: 10.1128/jcm.42.5.2255-2257.2004
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Microbiological Study of Subgingival Plaque by Real-Time PCR Shows Correlation between Levels of Tannerella forsythensis and Fusobacterium spp

Abstract: A TaqMan-based real-time PCR assay was established to quantify the periodontopathic bacteria Tannerella forsythensis and Fusobacterium spp. With this assay, the prevalence and proportion of these bacteria in clinical specimens were evaluated. Our preliminary results suggest a positive colocalization of T. forsythensis and Fusobacterium spp. in periodontal pockets.Periodontitis is thought to arise from the complex microflora consisting of putative periodontopathic bacteria, such as Porphyromonas gingivalis, Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 8 publications
3
31
0
4
Order By: Relevance
“…We showed that LAMP is suitable for rapid screening of oral bacteria and chairside diagnosis. Quantitative analysis of infectious disease pathogens is essential for accurate, detailed diagnosis (43,47,48). LAMP technology possesses the potential for quantitative analysis (25).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that LAMP is suitable for rapid screening of oral bacteria and chairside diagnosis. Quantitative analysis of infectious disease pathogens is essential for accurate, detailed diagnosis (43,47,48). LAMP technology possesses the potential for quantitative analysis (25).…”
Section: Discussionmentioning
confidence: 99%
“…Fusobacterium nucleatum is part of the “orange complex”, which is also associated with periodontal diseases (Socransky et al, 1998). F. nucleatum is a potent facilitator of periodontal aggregation (Jakubovics & Kolenbrander, 2010) and in some cases can constitute up to 20% or more of the bacteria in the subgingival biofilms (Suzuki et al, 2004). Aggregatibacter actinomycetemcomitans has been shown to be a potential etiological agent of an aggressive form of periodontitis particularly among adolescents from north and West Africa (Haubek et al, 2008).…”
mentioning
confidence: 99%
“…DNA from the samples was extracted using QuickGene DNA Tissue Kit S (Kurabo Industries, Osaka, Japan). Real-time polymerase chain reaction (PCR) was undertaken for specific sequences to detect four periodontal pathogens: Porphyromonas gingivalis, Treponema denticola, Tannerella forsythia, and Prevotella intermedia (11)(12)(13)(14).…”
Section: Methodsmentioning
confidence: 99%